Electromagnetic wave beam self - guidance in liquid crystal - semiconductor cell - Walczak, Andrzej (Photonics Letters of Poland, 2010)
A theoretical model and numerical results for a new kind of optical waveguide has been presented. The discussed waveguide is optically self-induced during light beam propagation along the boundary between a liquid crystal and a semiconducting polymer in an electrically driven lc cell. Experimental results obtained earlier are briefly reported here, and the theoretical model is discussed. The exploited liquid crystal was of birefringence close to 0.4. The photorefractive polymer was a poly (N-vinyl) carbazole doped with 2, 4, 7-trinitro-fluorenone. Full Text: PDF References H. Knobloch, H. Orendi, M. Buchel, T. Seki, S. Ito, W. Knoll,"Photochromic command surface induced switching of liquid crystal optical waveguide structures", J.Appl. Phys. 77, 481 (1995)[CrossRef] D.N. Christodoulides, R.I. Joseph,"Discrete self-focusing in nonlinear arrays of coupled waveguides", Opt.Lett. 13, 794 (1988)[CrossRef] A. Fratalocchi, G. Assanto, K.A. Brzdąkiewicz, M.A. Karpierz,"Discrete light propagation and self-trapping in liquid crystals", Opt. Expr. 13, 1808 (2005)[CrossRef] G. Assanto, A. Piccardi, A. Alberucci, S. Residori, U. Bortolozza,"Liquid Crystal Light Valves: a versatile platform for Nematicons", Phot. Lett. of Poland 1(4), 151 (2009) F. Sala, M. Karpierz,"Numerical simulation of beam propagation in a layer filled with chiral nematic liquid crystals", Phot. Lett. of Poland 1(4), 163 (2009) A. Spadlo, R. Dabrowski, J. Dziaduszek, S. Urban, E. Scibor, S. Gauza, S.T. Wu,"Liquid crystalline materials with high birefringence", J. Opt. Technol. 72, 659 (2005)[CrossRef] A. Walczak, E. Nowinowski-Kruszelnicki,"Polarization difference imaging system", ECLC Conference, Lisbona 2007 A. Walczak, E. Nowinowski-Kruszelnicki, Liquid Crystal Photonic Workshop, Cambridge 2008 Walczak, E. Nowinowski-Kruszelnicki,"Waveguide couplers induced optically over organic junction", Opt. Eng. 47(3) (2008)[CrossRef] N.V. Kukhtarev, S.F. Lyuksyutov, P. Buchhave, T. Kukhtareva, K. Sayano, P.P. Benerjee,"Self-enhancement of dynamic gratings in photogalvanic crystals", Phys. Rev. A 58, 4051 (1998)[CrossRef]